2019
DOI: 10.1097/cin.0000000000000586
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Emotional Well-being in Hospitalized Children and Adolescents With Virtual Reality

Abstract: The aim of this study was to describe and compare small-sized preliminary data on the usability and acceptability of a randomized controlled trial. This study compares a one-to-one cognitive-behavioral treatment and a virtual reality treatment for children and adolescents hospitalized for long-term physical conditions. The final sample was composed of 19 children and adolescents with chronic illness who were hospitalized. The sample was randomly allocated to two intervention groups: cognitive-behavioral usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Isolation from friends and peers is one of the most frequently reported negative aspects of hospitalization for adolescents [ 27 , 30 ]. Using VR to play games with friends or communicate with family via home-to-hospital live streaming [ 77 ] would therefore be particularly suitable for improving the mood and well-being of hospitalized adolescents, especially given their high level of enthusiasm and predisposition toward VR [ 16 , 20 ] and VR’s emerging acceptability for use in these settings [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation from friends and peers is one of the most frequently reported negative aspects of hospitalization for adolescents [ 27 , 30 ]. Using VR to play games with friends or communicate with family via home-to-hospital live streaming [ 77 ] would therefore be particularly suitable for improving the mood and well-being of hospitalized adolescents, especially given their high level of enthusiasm and predisposition toward VR [ 16 , 20 ] and VR’s emerging acceptability for use in these settings [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…VR is particularly appealing to adolescents; a recent US survey found that 73% of adolescents aged 11 to 15 years are fairly to extremely interested in VR [20]. Adolescents, defined by the World Health Organization as aged between 10 and 19 years [21], are developmentally distinct from young children and adults in terms of neurocognitive and physical maturation [22], yet studies of the use of VR for pediatric patients to date have primarily used samples that combined adolescents with young children [23][24][25][26], which makes it difficult to determine adolescent-specific outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Comfort is a pleasant sensation experienced by individuals and includes the physical, psychospiritual, social, and environmental aspects of a direct and comprehensive intervention 26 . Virtual reality interventions are more effective when compared with imagination techniques, and depth (the level of affecting sight sense) 27,28 and interaction with content can increase user attention and understanding so that they are positively correlated with specific emotional and health behaviors 15 . Virtual reality is an effective distraction method to reduce the individual's level of discomfort by conditioning the pain modulation process with an endogenous factor inhibition mechanism 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Virtual reality (VR) is a product of technological developments that allow users to be actively involved in the content viewed and to change the environment as expected 15 . The technique can also modify and create immersive, multisensory (virtual, auditory, tactile, and olfactory), and three-dimensional environments.…”
mentioning
confidence: 99%
“…El uso de juegos de realidad virtual tuvo un gran impacto en cuanto a la motivación para participar en actividades no farmacológicas, esto probablemente debido a la novedad que generan, lo cual abrió la posibilidad a utilizar los contextos virtuales también como herramientas para la intervención psicológica (Flujas-Contreras et al, 2020). En esta categoría, cabe mencionar el estudio de Arnon y colaboradores (2018), que utilizó un video con técnicas de hipnosis para reducir la ansiedad y dolor percibido a partir de la invitación a los pacientes al uso de la imaginación previo al procedimiento médico, obteniendo los resultados esperados.…”
Section: La Tecnología Para Jugarunclassified